A Family of Zero-Voltage-Transition Magnetic Coupling Bidirectional DC/DC Converters - Shanshan Wang; Ming Gao; Jianjiang Shi (Energies, 2023)
In this paper, a family of zero-voltage-transition (ZVT) magnetic coupling bidirectional DC/DC converters (BDCs) is proposed. The coupling inductor has two functions: to serve as a filter; and to provide the auxiliary current. In addition, the phase-shifting control method is used to reduce the conduction loss of the auxiliary circuit. The auxiliary switches are all working under zero-current-switching (ZCS) conditions; thus, all the switches have no switching loss. Furthermore, compared with the traditional ZVT implementation method based on the coupled inductor, this topology avoids the input source current notch and has a smaller ripple. Finally, a prototype of 800 W BDC is built to verify the feasibility of the proposed topology.